Recent Insight into SARS-CoV2 Immunopathology and Rationale for Potential Treatment and Preventive Strategies in COVID-19 - Sara Lega (Vaccines, 2020)
As the outbreak of the new coronavirus (SARS-CoV-2) infection is spreading globally, great effort is being made to understand the disease pathogenesis and host factors that predispose to disease progression in an attempt to find a window of opportunity for intervention. In addition to the direct cytopathic effect of the virus, the host hyper-inflammatory response has emerged as a key factor in determining disease severity and mortality. Accumulating clinical observations raised hypotheses to explain why some patients develop more severe disease while others only manifest mild or no symptoms. So far, Covid-19 management remains mainly supportive. However, many researches are underway to clarify the role of antiviral and immunomodulating drugs in changing morbidity and mortality in patients who become severely ill. This review summarizes the current state of knowledge on the interaction between SARS-CoV-2 and the host immune system and discusses recent findings on proposed pharmacologic treatments.